2020
DOI: 10.3390/ijms21030954
|View full text |Cite
|
Sign up to set email alerts
|

Killer Immunoglobulin-Like Receptor 2DL4 (CD158d) Regulates Human Mast Cells both Positively and Negatively: Possible Roles in Pregnancy and Cancer Metastasis

Abstract: Killer immunoglobulin-like receptor (KIR) 2DL4 (CD158d) was previously thought to be a human NK cell-specific protein. Mast cells are involved in allergic reactions via their KIT-mediated and FcɛRI-mediated responses. We recently detected the expression of KIR2DL4 in human cultured mast cells established from peripheral blood of healthy volunteers (PB-mast), in the human mast cell line LAD2, and in human tissue mast cells. Agonistic antibodies against KIR2DL4 negatively regulate the KIT-mediated and FcɛRI-medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 101 publications
1
10
0
Order By: Relevance
“…The possible participation in the initiation of pregnancy has been linked with the presence of the KIR2DL4 receptor. However, it is not conclusive as positive and no-effect studies can be found in the literature [89,90]. A recent meta-analysis of data from articles from the databases like Web of Science, PubMed, Scopus, Google Scholar, etc.…”
Section: Kir/hla Interaction In Pregnancy Complicationmentioning
confidence: 99%
“…The possible participation in the initiation of pregnancy has been linked with the presence of the KIR2DL4 receptor. However, it is not conclusive as positive and no-effect studies can be found in the literature [89,90]. A recent meta-analysis of data from articles from the databases like Web of Science, PubMed, Scopus, Google Scholar, etc.…”
Section: Kir/hla Interaction In Pregnancy Complicationmentioning
confidence: 99%
“…These 'HLA-G/KIR2DL4' combinations are able to result in the production of pro-inflammatory cytokines like IFN-g for driving cells into an immunosuppressive phase (134). KIR2DL4 could be also observed in mast cells recently (135). It was involved in Janus kinase-signal transducer and activator of transcription (JAK/STAT) signaling pathway association with trophoblast invasion and angiopoiesis by HTR-8/SVneo cell line.…”
Section: Hla-g Acting In the Pregnancy Microenvironmentmentioning
confidence: 99%
“…Unlike other KIR receptors, the KIR2DL4 receptor has inhibitory and activator properties [21][22][23]. The KIR2DL4 receptor can be activated by recombinant HLA-G (major histocompatibility complex, class I, G)or agonistic antibodies, such as KIR2DL4 clones mAb 33 and mAb 181703 [24][25]. Stimulating the activator signals of NK cells increases their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%